Cognitive, socioemotional, and behavioural returns to college quality - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
We exploit the variation in the admissions process across colleges of a leading Indian university to estimate the causal effects of enrolling in a selective college on: cognitive attainment using scores on standardized university exams; behavioural preferences such as risk, competitiveness, and overconfidence; and socioemotional traits using measures of Big Five personality. Using a regression discontinuity design, we find that enrolling in a selective college leads to improvements in females' exam scores with no effect on males' scores. Marginally admitted females in selective colleges become less overconfident and less risk averse as compared to their counterparts in the less selective colleges. Males in selective colleges experience a decline in extraversion and conscientiousness. We find higher attendance rates among females to be one of the likely channels explaining the gender differences in returns to better college and peer environment. To the best of our knowledge, this is the first paper in the literature to go beyond cognitive outcomes, to causally identify the returns to college quality on both behavioural and socioemotional traits.
Keywords: I23; C9; C14; J24; O15; 330; cognitive attainment; behaviour; personality; college quality; peer effects; India